2018
DOI: 10.1534/genetics.117.300480
|View full text |Cite
|
Sign up to set email alerts
|

Functional Redundancy of Variant and Canonical Histone H3 Lysine 9 Modification in Drosophila

Abstract: Histone post-translational modifications (PTMs) and differential incorporation of variant and canonical histones into chromatin are central modes of epigenetic regulation. Despite similar protein sequences, histone variants are enriched for different suites of PTMs compared to their canonical counterparts. For example, variant histone H3.3 occurs primarily in transcribed regions and is enriched for "active" histone PTMs like Lys9 acetylation (H3.3K9ac), whereas the canonical histone H3 is enriched for Lys9 met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…To further explore potential male-specific functions of H3.3B lysine 27, we introduced a transgene containing the wild type H3 . 3B gene onto chromosome three [47] ( Fig 3D ). The additional wild type copy of H3.3B fully rescued viability of H3.3B K27R males ( Fig 3E ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore potential male-specific functions of H3.3B lysine 27, we introduced a transgene containing the wild type H3 . 3B gene onto chromosome three [47] ( Fig 3D ). The additional wild type copy of H3.3B fully rescued viability of H3.3B K27R males ( Fig 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis was performed essentially as described previously [47]. Briefly, the H3.3B lysine 27 to arginine substitution was made using a single gRNA (TGCCCGTAAGTCGACCGGAGGAAAGG) inserted into pCFD3 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies that investigated the function of histone H3 modifications by histone replacement genetics showed that for modifications associated with transcriptionally active chromatin it is essential to remove not only the wild-type copies of the canonical histone genes but to also mutate the histone H3.3 variants (23, 24). The analyses of H4K16R , H4K16Q , and H4K16A mutant phenotypes reported here were all performed in the genetic background of animals lacking His4r, the only histone H4 variant in Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…Currently >150 distinct genetic loci are reported to impact PEV, highlighting the complexity of heterochromatin control. Critically, the pathway depositing H3K9me2/3-HP1a forms the regulatory core and null mutations in Su(var) 2-5 (HP1a), and replacement of H3K9 with arginine (H3K9R) to block its modification is lethal (Eissenberg et al 1990;Penke et al 2016Penke et al , 2018. The Drosophila genome encodes three K9 methyltransferases-Su(var)3-9, eggless/SetDB1, and G9a-and all three have been reported to modify PEV (Mis et al 2006;Brower-Toland et al 2009).…”
mentioning
confidence: 99%